Dal pluralismo politico allo Stato plurale (ovvero della democrazia al tempo dei populismi e degli etno-nazionalismi) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
What about political pluralism in the contemporary State, in an era in which the reawakening of cultural and ethnic identities coexists with a growing diffusion of new nationalisms? Disguised as sovereignism and populism, such new versions of nationalism try to bring the concept of “people” back to the idea of “organic community”, as the purported socio-political foundation of “true democracy”. Nevertheless, this concept, has proved to be, on the contrary, the ideological basis of totalitarianism. In a global scenario of growing tension between unity and plurality, with opposite examples in a continuum that goes from the experimentation of “plural States” and “plurinational Republics” to the reaffirmation of  the so called “ethnic State”, this article aims to regain an analytical perspective on the concept of pluralism, that has never ceased to be - and still is - inseparably linked with the idea and practice of democracy